Conservation of Agroecosystem through Utilization of Parasitoid Diversity: Lesson for Promoting Sustainable Agriculture and Ecosystem Health - DAMAYANTI BUCHORI; BANDUNG SAHARI; NURINDAH NURINDAH (HAYATI Journal of Biosciences, 2008)
For many years, agricultural intensification and exploitation has resulted in biodiversity loss and threaten ecosystem functioning. Developing strategies to bridge human needs and ecosystem health for harmonization of ecosystem is a major concern for ecologist and agriculturist. The lack of information on species diversity of natural enemies and how to utilize them with integration of habitat management that can renovate ecological process was the main obstacle. Parasitoids, a group of natural enemies, play a very important role in regulating insect pest population. During the last ten years, we have been working on exploration of parasitoid species richness, how to use it to restore ecosystem functions, and identifying key factors influencing host-parasitoid interaction. Here, we propose a model of habitat management that is capable of maintaining agricultural biodiversity and ecosystem functions. We present data on parasitoid species richness and distribution in Java and Sumatera, their population structure and its impact toward biological control, relationship between habitat complexes and parasitoid community, spatial and temporal dynamic of parasitoid diversity, and food web in agricultural landscape. Implications of our findings toward conservation of agroecosystem are discussed. Key words: conservation, agroecosystem, parasitoid, diversity, ecosystem health